PENERAPAN PENILAIAN KINERJA PADA MATERI TRANSFORMASI ENERGI DI SEKITAR KITA DENGAN MODEL PROJECT BASED LEARNING (PJBL) UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV DI SDN PENGKOL 01 - Andres Alam Dewangga; Veronika Unun Pratiwi; Agus Sri Antana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the application of performance assessment on the material of energy transformation around us with the Project Based Learning (PjBL) model to improve the learning outcomes of grade IV students of SD N Pengkol 01. This study uses a Classroom Action Research design with the Kemmis & Taggart model consisting of 4 stages, namely: (1) Planning stage, (2) Implementation stage, (3) Observation stage, and (4) Reflection stage carried out in two cycles. The subjects used in this study were 24 grade IV students of SD N Pengkol 01. The types of data used are quantitative and qualitative data. The results of the study showed an increase in learning outcomes. The average class value in cycle I reached a completion percentage of 46% and increased in cycle II by 83%. So, it can be concluded that the application of performance assessment on the material of energy transformation around us with the Project Based Learning model can improve the learning outcomes of fourth grade students at SDN Pengkol 01